Does mode of delivery impact the course of cervical dysplasia in pregnancy? A review of 219 cases. (July 2022) - Bracic, Taja; Reich, Olaf; Taumberger, Nadja; Tamussino, Karl; Trutnovsky, Gerda
Highlights: HSIL in pregnancy has high persistence rates (70%). Progression of dysplasia to invasive disease in pregnancy is rare (2 out of 219 women). HPV-Infection persisted in a high number of cases during pregnancy. Mode of delivery is not associated with regression rates of cervical dysplasia. Abstract: Objective: The prevalence of cervical intraepithelial neoplasia (CIN) in pregnancy is about 1%. The aim of this study was to analyze the regression, persistence and progression rates of cervical dysplasia in pregnancy and the impact of delivery mode. Study design: In this retrospective study, data from pregnant patients with abnormal cytology findings, who presented to a colposcopic outpatient clinic of a university hospital within the last 10 years, were analyzed. Information on cytology, histology and Human Papillomavirus (HPV) status during pregnancy and postpartum and mode of delivery was collected. Results: 219 women, who were assessed with cytology and /or biopsy antepartum and postpartum between January 2010 and July 2020, were included in the study. Antepartum patients presented with low grade squamous intraepithelial lesions (LSIL) in 37% and high grade squamous intraepithelial lesions (HSIL) in 53%. During pregnancy biopsy was performed in 78 patients (36%). Postpartum evaluation revealed an overall regression rate of 39%. Persistence rates were especially high in the HSIL group with 70 %. HSIL regressed in 28 %. Progression to invasive disease was rare and seen in two patients postpartum only. 141 women delivered vaginally (VD) and 51 received a cesarean section (CS). Regression rates were similar: 36 % and 47 %. There was no significant difference in progression or persistence rates. Conclusion: Our study demonstrates that mode of delivery does not influence the course of SIL. SIL show high rates of regression and persistence, progression to invasive disease is rare.